A Master Regulator BrpR Coordinates the Expression of Multiple Loci for Robust Biofilm and Rugose Colony Development in Vibrio vulnificus - Hwang, Seung-Ho; Im, Hanhyeok; Choi, Sang Ho (Frontiers in Microbiology, 2021)
Vibrio vulnificus, a fulminating human pathogen, forms biofilms to enhance its survival in nature and pathogenicity during host infection. BrpR is the transcriptional regulator governing robust biofilm and rugose colony formation in V. vulnificus, but little is known about both the direct regulon of BrpR and the role of BrpR in regulation of downstream genes. In this study, transcript analyses revealed that BrpR is highly expressed and thus strongly regulates the downstream gene in the stationary and elevated cyclic di-GMP conditions. Transcriptome analyses discovered the genes, whose expression is affected by BrpR but not by the downstream regulator BrpT. Two unnamed adjacent genes (VV2_1626-1627) were newly identified among the BrpR regulon and designated as brpL and brpG in this study. Genetic analyses showed that the deletion of brpL and brpG impairs the biofilm and rugose colony formation, indicating that brpLG plays a crucial role in development of BrpR-regulated biofilm phenotypes. Comparison of the colony morphology and exopolysaccharide (EPS) production suggested that although the genetic location and regulation of brpLG are distinct from the brp locus, brpABCDFHIJK (VV2-1574-1582), brpLG is also responsible for the robust EPS production together with the brp locus genes. Electrophoretic mobility shift assays and DNase I protection assays demonstrated that BrpR regulates the expression of downstream genes in distinct loci by directly binding to their upstream regions, revealing a palindromic binding sequence. Altogether, this study suggests that BrpR is a master regulator coordinating the expression of multiple loci responsible for EPS production and thus, contributing to the robust biofilm and rugose colony formation of V. vulnificus.